2020
DOI: 10.1093/eurheartj/ehaa172
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides and remnant cholesterol associated with risk of aortic valve stenosis: Mendelian randomization in the Copenhagen General Population Study

Abstract: Aims We tested the hypothesis that higher levels of plasma triglycerides and remnant cholesterol are observationally and genetically associated with increased risk of aortic valve stenosis. Methods and results We included 108 559 individuals from the Copenhagen General Population Study. Plasma triglycerides, remnant cholesterol (total cholesterol minus low-density lipoprotein and high-density lipoprotein cholesterol), and 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 64 publications
1
56
0
1
Order By: Relevance
“…β2GPI activates lipoprotein lipase and triglyceride-rich lipoprotein (TRL) catabolism [ 61 ]. High TRL levels have recently been linked with CAVS [ 62 ]. β2GPI was found to associate with ox-LDL [ 63 ] and, more interestingly, to Lp(a) particles [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…β2GPI activates lipoprotein lipase and triglyceride-rich lipoprotein (TRL) catabolism [ 61 ]. High TRL levels have recently been linked with CAVS [ 62 ]. β2GPI was found to associate with ox-LDL [ 63 ] and, more interestingly, to Lp(a) particles [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of steatosis, TG elevations are in particular associated with coronary plaques, both calcified and non‐calcified, as well as with non‐obstructive coronary stenoses 110 . Besides being correlated per se with calcified plaques independent of the presence of the metabolic syndrome in NAFLD patients, 111 higher TG and remnant cholesterol have been observationally and genetically associated with an increased risk of aortic valve stenosis 112 . Overall, the association between serum TG and hepatic steatosis is largely accounted for by a greater TG enrichment in VLDL particles 113 .…”
Section: Nafld and Risk Of Cardiovascular Diseasesmentioning
confidence: 99%
“…In the multifactorial adjusted analyses, higher concentrations of triglycerides and remnants were observationally and genetically linked to a higher rate of aortic valve stenosis. A novel etiopathogenic factor in aortic valve stenosis that warrants further research has been indicated by these findings [ 54 ].…”
Section: An Insight Into Other Implications Of Hypertriglyceridemia Beyond Atherosclerosismentioning
confidence: 99%